Pre-Service English Teachers’ Knowledge of Integrating Science, Technology, Engineering, Art, And Mathematics (STEAM) In English Language Teaching (ELT) - Nabila Tritania Pujaningsih; Santhy Hawanti (UM Purwokerto Press, 2026)
The research examines the pre-service English teachers’ knowledge levels of integrating STEAM (Science, Technology, Engineering, Arts, and Mathematics) in English Language Teaching (ELT). The study was conducted at Universitas Muhammadiyah Purwokerto and involved 27 respondents from the 8th-semester English education program. The research utilized a quantitative approach, employing a questionnaire based on the Guttman scale to assess knowledge levels. Findings reveal that most respondents (22 out of 27) possess a high level of knowledge regarding STEAM integration in ELT, with scores ranging from 76% to 100%. Three respondents demonstrated medium knowledge (56% to 75%), while two exhibited low knowledge (below 56%). The average knowledge score among participants was 89.8%. This indicates that more than half of the sample has a high level of STEAM knowledge.